When ghosts come home [compact disc, unabridged] : a novel - Cash, Wiley (Harper Audio, 2021)
When the roar of a low-flying plane awakens him in the middle of the night, Sheriff Winston Barnes knows something strange is happening at the nearby airfield on the coast of North Carolina. But nothing can prepare him for what he finds: a large airplane has crash-landed and is now sitting sideways on the runway, and there are no signs of a pilot or cargo. When the body of a local man is discovered, shot dead and lying on the grass near the crash site, Winston begins a murder investigation that will change the course of his life and the fate of the community that he has sworn to protect. Everyone is a suspect, including the dead man. As rumors and accusations fly, long-simmering racial tensions explode overnight, and Winston, whose own tragic past has followed him like a ghost, must do his duty while facing the painful repercussions of old decisions. Winston also knows that his days as sheriff may be numbered. He's up for re-election against a corrupt and well-connected challenger, and his deputies are choosing sides. As if these events weren't troubling enough, he must finally confront his daughter Colleen, who has come home grieving a shattering loss she cannot fully articulate.